2021
DOI: 10.3390/polysaccharides2010010
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Regenerated Cellulose Fibers Sourced from Recycled Cotton T-Shirt Using Glucaric Acid for Antiplasticization

Abstract: The recycling of cellulose from cotton textiles would minimize the use of virgin crop fibers, but recycled polymers are generally inferior in mechanical performance to those made from virgin resins. This challenge prompted the investigation of biobased additives that were capable of improving the mechanical properties of fibers by means of antiplasticizing additives. In this study, regenerated cellulose (RC) fibers were spun from cellulose found in cotton T-shirts, and fibers were mechanically strengthened wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…According to Awal and Sain, the addition of PEO at 5-20 wt%, plasticized the melt spinning of soda hardwood lignin (SHL). The melt spinning temperature reduced by 10 • C at 20 wt% PEO and observed higher drawing speeds when compared to the neat SHL system-but did not mention spinning draw ratio [2,3].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to Awal and Sain, the addition of PEO at 5-20 wt%, plasticized the melt spinning of soda hardwood lignin (SHL). The melt spinning temperature reduced by 10 • C at 20 wt% PEO and observed higher drawing speeds when compared to the neat SHL system-but did not mention spinning draw ratio [2,3].…”
Section: Introductionmentioning
confidence: 93%
“…Recent efforts to meet the emerging demand for high-performance fibers and industrial fibers have focused on the development of high-volume and high-end products from biopolymers. Industrial fibers from natural resources are competitive alternatives of petroleum-sourced synthetic fibers due to high abundancies, biodegradability, non-toxicity, and low cost [1][2][3]. Lignin, the most abundant aromatic biopolymer and waste by-product of pulp and paper mills, showed promising performance as a biorenewable alternative to petroleum-based, expensive raw materials for carbon fiber manufacturing [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to NMMO technology, the NaOH/urea solvent system shows noticeable results regarding similar fiber properties but with lower production costs. 116 Alkali/urea aqueous has been utilized as an environmentally friendly alternative for cellulose dissolution systems. Liu et al 39 compared two solvent systems, LiOH/urea and NaOH/urea, for their efficacy in dissolving cotton waste and regenerating cellulose fibers.…”
Section: Mixed Knitted Fabrics [91]mentioning
confidence: 99%
“…However, reports say recycled polymers are generally inferior in mechanical performance compared to conventional processes; hence, strengthening additives are required to achieve the desired properties for regenerated fibers. Biswas et al 116 reported recycling cotton waste pulp using LiCl/DMAc activated using aqueous sodium hydroxide and then followed by acid neutralization to strengthen the mechanical properties.…”
Section: Mixed Knitted Fabrics [91]mentioning
confidence: 99%
See 1 more Smart Citation